GENETIC STABILITY ANALYSIS OF RB GENE IN GENETICALLY MODIFIED POTATO LINES TOLERANT TO Phytophthora infestans - Edy Listanto; Eny Ida Riyanti; Tri Joko Santoso; Toto Hadiarto; A. Dinar Ambarwati (Indonesian Agency for Agricultural Research and Development, 2015)
Development of potato cultivars with high levels of broad spectrum resistance is a key long-term management strategy against late blight disease caused by Phytophthora infestans. Six progeny lines of hybridization between transgenic potato Katahdin SP951 with non-transgenic Granola and Atlantic were selected based on agronomical characteristics and resistance to late blight disease. The study aimed to analyze the number of insertions and stability of inserted RB gene in the transgenic potato lines. The research was carried out through plant DNA extraction, southern blot analysis and polymerase chain reaction (PCR). Southern blot analysis was used to detect the number of inserts integrated into potato genome, while PCR analysis was used to detect stability of RB gene from generation to generation. The results showed that the progenies obtained from hybridization between Atlantic and transgenic Katahdin SP951 (lines No. 20 and 27) and between Granola and transgenic Katahdin SP951 (line No. 69) contained one copy number of RB gene, according to the probing of nptII. The result is similar to that of inserted RB gene found in the parental transgenic Katahdin SP951. The presence of RB gene in four different generations (G0, G1, G2 and G3) showed stable integration of the gene into the plant genome. The single copy number of RB gene will repress the occurrence of silencing gene expression. The stability analysis of RB gene can determine that the gene is still present in plant genome after several generations.